The Introduction Of the Balinese Script Through Playworld for The Early Children With The Tri Hita Karana Approach - Putu Dina Yuniarini (Universitas Panca Sakti Bekasi, 2023)
Some children were fearful when participating in learning activities at school. It was due to the less pleasant learning activities, giving an impact on decreasing students’ enthusiastic on learning. This study aimed to analyze Playworld by using the Tri Hita Karana (THK) approach to introduce the Balinese script in early childhood. The type of the research was qualitative research using pre-experimental methods. The pre-experimental design with a one-group pretest and post-test design was used as the research design. The research population was 38 children. The number of samples used were 15 children. The observation and interview methods were used to collect the data. The questionnaire was used as the data collection instrument. The data analysis technique used in this study was statistical analysis. The results of the t-test showed 0.00 <0.05, so there was a difference in the average results of introducing Balinese script to the early children after implementing Playworld with the THK approach. It was concluded that implementing the Playworld by using the THK approach, could help young children learn the Balinese script. The study implies that the Playworld with the THK approach can be applied in learning so that children can be more eager to participate in learning and increase their understanding